Germination of Tisuk (Hibiscus macrophyllus Roxb.) Seed at Several Treatments of Lighting Period, Pre-germination and Storage - Dede J. Sudrajat; Yulianti Bramasto (Jurnal Perbenihan Tanaman Hutan, 2018)
Tisuk (Hibiscus macrophyllus Roxb.) is a potential fast growing species to cultivate in a forest community and forest plantation. This species has strong seed dormancy that causing  its germination becomes obstacle in seedling procurement. The aim of this research was to determine the response of tisuk seed germination on the several lighting periods, pre-germination treatment, and storage rooms by using 4 tisuk populations (Sumedang, Ciamis, Pemalang and Malang) in Java.  Randomized completely design was used to test the optimum lighting periods, pre-germination treatments, and storage rooms for tisuk seeds. The result showed that lighting periods was the only treatment which affected significantly the seedlot from Pemalang. Seed germination testing of tisuk in laboratory was preferred to use lighting period of 8 hours light and 16 hours dark. Tisuk seed is categorized as orthodox with strong dormancy level so the seed germination capacity and speed without pre-germination treatment were very low that is  ranged between  5.5 percent ─̶ 8.3 percent and 0.62 percent-etmal─̶ 0.91percent-etmal, respectively. Pre-germination treatment by soaking the seeds in  H2SO4 for 30 minutes was able to increase germination capacity and speed for all seedlots from 4 different populations with germination capacity and speed ranges of 62.5 percent ─̶ 71.3 percent and 7.58 percent-etmal ─̶ 9.75 percent-etmal, respectively. Tisuk seed of all the  populations were  deteriorating during storage and seed with the lower moisture content had better storability. The seed germination could be maintained better in Dry Cold Storage than in a refrigerator and ambient room.